Spatial structure of neighbourhoods of small and large trees in Gambari Natural Forest Reserve, Nigeria (2025)
Structure of forest is spatially and temporally dynamic and therefore, effective prediction of structural diversity is difficulty. Correlation between spatial species diversity and size inequality regulates structure of tree community. Hence, estimation of tree structure around small and large tree sizes will provide understanding on process regulating tree distribution in Gambari Natural Forest Reserve. Therefore, the study was designed to investigate neighbourhood structure of small and large trees in Gambari Natural Forest Reserve, Oyo State. Two parallel line transects ranged 800 m to 1km long separated by 50 m were demarcated in Gambari Natural Forest Reserve. At least, four (30m x 30m) sample plots were established systematically on each transect. Minimum and Maximum DBH stems were selected at the centre of the plots, designated as Small and Large reference trees, respectively. A circular subplot (radius=10m; 314.2m2) was established around reference tree. Trees with diameter at breast height (DBH) ≥5 cm were enumerated, identified to species level, and DBH and their distances to reference tree were measured in each subplot. The species diversity indices of trees in each subplot were computed. Data collected were analysed using Descriptive statistics, Clark and Evans index. Species mingling and Diameter differentiation indices at α0.05. A total of 26 and 21 tree species was identified in the subplots of Large and Small reference trees, respectively. The species diversity indices (H´=3.0, 1-D =0.94 and M=6.24) around Large reference trees were higher than (H´=2.69, 1-D=0.91 and M = 4.99) of Small reference trees. Strombosia pustulata and Hildegardia barteri, and Strombosia pustulata and Triplochiton scleroxylon were the dominant tree species around Large and Small reference trees, respectively. Hundred percent (100%) and (55.56%) of subplots of Large and Small reference trees expressed regular pattern at 10m distance. The proportion of heterospecifics of Large reference trees was higher than Small at highest mingling value. Smallest DBH trees were less than 50% and 40% size around Large and Small reference trees, respectively. Trees with smallest DBH were less than 50% and 40% tree size around most of Large and Small reference trees, respectively. Neighbourhood of Large reference trees exhibited structural heterogeneity than Small reference trees.